The Palgrave Handbook of Practical Animal Ethics (The Palgrave Macmillan Animal Ethics Series, 2018)
This handbook provides an in-depth examination of the practical and theoretical issues within the emerging field of animal ethics. Leading experts from around the globe offer insights into cutting edge topics as diverse as killing for food, religious slaughter, animal companions, aquariums, genetic manipulation, hunting for sport and bullfighting. Including contributions from Lisa Johnson on the themes of human dominance, Thomas White on the ethics of captivity, Mark Bernstein on the ethics of killing and Kay Peggs on the causation of suffering, this handbook offers an authoritative reference work for contemporary applied animal ethics. Progressive in approach, the authors explore the challenges that animal ethics poses both conceptually and practically to traditional understandings of human-animal relations. Key Features: · Structured in four parts to examine the ethics of control, the ethics of captivity, the ethics of killing and the ethics of causing suffering · Interdisciplinary approach including philosophical, historical, scientific, legal, anthropological, religious, psychological and sociological perspectives · Focussed treatment of practical issues such as animals in farming, zoos and animal experimentation The Palgrave Handbook of Practical Animal Ethics is an essential resource for those with an interest in the ethics of modern-day treatment of animals as well as scholars, researchers and advanced students in zoology, philosophy, anthropology, religious studies and sociology.